Marine Heatwaves and Cyclone Interactions in the North Indian Ocean: A Tale of Shaheen and Gulab - Pukkalla, Tarakeshwar; Kailasam, Muni Krishna (Earth and Planetary Science, 2025)
Tropical cyclones (TCs) are among the most devastating natural hazards, and their development can be significantly influenced by marine heatwaves (MHWs)—periods when sea surface temperatures (SSTs) rise 3–4 °C above average for at least five days. This study investigates the interaction between TCs Gulab and Shaheen and MHW conditions in the North Indian Ocean during September–October 2021. Using data from NOAA‑OISST and HYCOM model outputs, along with the Marine Heatwave Tracker, we mapped the timeline of MHWs relative to the formation and intensification of these cyclones. TC Gulab originated in the Bay of Bengal and later redeveloped as TC Shaheen in the Arabian Sea—an uncommon occurrence during the southwest monsoon season. On average, 1–2 cyclones form annually in the Arabian Sea, and about 48.5% dissipate without making landfall. However, TC Shaheen intensified into a Severe Cyclonic Storm (SCS) and made landfall on Oman’s coast, where persistent MHWs were observed. The study suggests that elevated SSTs due to MHWs played a significant role in sustaining and intensifying the storm system. These findings highlight the importance of understanding oceanic thermal anomalies in assessing cyclone behavior and potential landfall impacts, especially in the context of a warming climate and increasing frequency of extreme marine heat events. ER